Development of Cross-sectional Competences at Universidad de Murcia: Strengths, Weaknesses, and Proposals for Improvement - González Morga, Natalia (2018)
The development of cross-sectional competences in higher education is of special interest because of its link to the socio-labor context. The inclusion of these competences in the university curriculum is irregular and complex. Teamwork, social interaction, ethical-social commitment, and emotional control are, among others, key competences of professionals nowadays. The aim of this work is to ascertain the degree of development of these four cross-sectional competences and to identify the strengths and weaknesses in their training process, and finally to analyze the proposals for improvement provided by 1,137 students in their final year of undergraduate studies from the five branches of knowledge at Universidad de Murcia. The CECTGRA questionnaire was applied and its answers were analyzed from a mixed approach alternating the use of the SPSS v23 and ATLAS.TI 7 programs. The results point out towards the need to improve the development of competences; teamwork is the most developed, with emotional control at the opposite end, with significant differences among each branch of knowledge. The strengths identified are grouped in relation to students themselves, the environment, and the structure; and the weaknesses and proposals for improvement revolving on the institution, the center, and the classroom.